Discrete event simulation of healthcare systems - Meng, Le Yin. (2008)
The objective of this project is to demonstrate the use of simulation methodology to assist in decision making in the healthcare sector, with special reference to a outpatient radiology clinic in Singapore and an accident and emergency department in UK.